IMPLEMENTASI BAURAN PEMASARAN SYARIAH PADA KOSMETIK BERLABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PERSPEKTIF ISLAM - Khodijah, Siti; Muhammad Iqbal Fasa,; Suharto, Suharto (Juremi: Jurnal Riset Ekonomi, 2023)
Cosmetics comes from the Greek word “kosmetikos” which means skill to decorate, arrange. The definition of cosmetics in the Regulation of the Minister of Health of the Republic of Indonesia No. 445/MenKes/Permenkes/1998, namely cosmetics are preparations or combinations of materials that are ready to be used on the outside of the body to change the appearance but not to cure a disease. This study aims to determine how the influence of the marketing mix on consumer decisions in buying halal cosmetic products. This study uses qualitative methods with data sources, namely secondary data, in the form of literature review. The results of this study indicate that the marketing mix has an influence on consumer purchasing decisions, namely with a good strategy for the marketing mix such as improving product quality, affordable prices, attractive promotional strategies and smooth distribution will influence consumer decisions in buying a product or item.